In vivo MR guided boiling histotripsy in a mouse tumor model evaluated by MRI and histopathology. (7th April 2016) - Hoogenboom, Martijn; Eikelenboom, Dylan; den Brok, Martijn H.; Veltien, Andor; Wassink, Melissa; Wesseling, Pieter; Dumont, Erik; Fütterer, Jurgen J.; Adema, Gosse J.; Heerschap, Arend
Abstract : Boiling histotripsy (BH) is a new high intensity focused ultrasound (HIFU) ablation technique to mechanically fragmentize soft tissue into submicrometer fragments. So far, ultrasound has been used for BH treatment guidance and evaluation. The in vivo histopathological effects of this treatment are largely unknown. Here, we report on an MR guided BH method to treat subcutaneous tumors in a mouse model. The treatment effects of BH were evaluated one hour and four days later with MRI and histopathology, and compared with the effects of thermal HIFU (T‐HIFU). The lesions caused by BH were easily detected with T 2 w imaging as a hyper‐intense signal area with a hypo‐intense rim. Histopathological evaluation showed that the targeted tissue was completely disintegrated and that a narrow transition zone (<200 µm) containing many apoptotic cells was present between disintegrated and vital tumor tissue. A high level of agreement was found between T 2 w imaging and H&E stained sections, making T 2 w imaging a suitable method for treatment evaluation during or directly after BH. After T‐HIFU, contrast enhanced imaging was required for adequate detection of the ablation zone. On histopathology, an ablation zone with concentric layers was seen after T‐HIFU. In line with histopathology, contrast enhanced MRI revealed that after BH or T‐HIFU perfusion within the lesion was absent, while after BH in the transition zone some micro‐hemorrhaging appeared. Four days after BH, the transition zone with apoptotic cells was histologically no longer detectable, corresponding to the absence of a hypo‐intense rim around the lesion in T 2 w images. This study demonstrates the first results of in vivo BH on mouse tumor using MRI for treatment guidance and evaluation and opens the way for more detailed investigation of the in vivo effects of BH. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : An in vivo MR guided boiling histotripsy (BH) set‐up is developed for the treatment of subcutaneous mouse tumors. With BH, the tissue is fragmentized into submicron fragments, without significant hemorrhages and with a sharp transition zone (<200 µm) between disintegrated and vital tissue. Both one hour and four days post treatment, among T 1 w, T 2 w, PDw and DCE imaging, T 2 w imaging was found to be the best method for treatment planning and evaluation.